Assessment of Inter-modality Spatial Alignment Accuracy in Hybrid Single Photon Emission Computed Tomography in Patients with Hand and Wrist Pain - Cheng Xie; Gopinath Gnanasegaran; Hosahalli Mohan; Lefteris Livieratos (World Journal of Nuclear Medicine)
Single photon emission computed tomography (SPECT) and computed tomography (CT) integrated in one system (SPECT/CT) is an effective co-registration technique that helps to localize and characterize lesions in the hand and wrist. However, patient motion may cause misalignment between the two modalities leading to potential misdiagnosis. The aim of the present study was to evaluate the hardware-based registration accuracy of multislice SPECT/CT of the hand and wrist and to determine the effect of misalignment errors on diagnostic accuracy. A total of 55 patients who had multislice SPECT/CT of the hand and wrist between July 2008 and January 2010 were included. Two reviewers independently evaluated the fused images for any misalignments with six degrees of freedom: Translation and rotation in the X, Y and Z directions. The results were tested against an automated fusion tool (Syntegra). More than half of the patients had moved during SPECT scanning (Reviewer 1: 29 patients; Reviewer 2: 30 patients) and they all originated in the Y-direction translation (vertical hand motion). Five fused images had significant misalignment errors that could have led to misdiagnosis. The Wilcoxon test indicated statistically non-significant difference (P > 0.05) between reviewers and statistically non-significant difference between the reviewers and software registration. The study also showed high inter-reviewer agreement (κ = 0.87). Hand movement during the SPECT scan was common, but significant misalignments and subsequent misdiagnosis were infrequent. Future studies should investigate the use of hand and wrist immobilization devices and reductions of scan time to minimize patient motion.